Added Value Analysis of Bandeng Fish (Chanos chanos) Amplang Business in Babulu Laut Village, North Penajam Paser Regency - Qur’ain, Siti Paturahmah; Haqiqiansyah, Gusti; Oktawati, Nurul Ovia (Jurnal Media Akuakultur Indonesia, 2024)
Bandeng fish amplang processing in Babulu Laut Vilage is still classified as a small household business, with 7 amplang processors in Babulu Laut Village. This research was conducted to determine the value added of the bandeng fish amplang business in Babulu Laut Village. The number of respondents was 7 people, so the researcher took the entire population as a sample (census). The results showed that the added value of raw bandeng fish processed into amplang was Rp. 198,553 per kg with a value added ratio of 66%. This value added ratio is considered high because it is more than 10%. The profit margin of the bandeng fish amplang was Rp. 270,865 with a profit of 69 that had been distributed to each individual such as labor income of 4% and other input contributions of 27%.